2020
DOI: 10.3390/ani10030368
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A Inhibits Ruminal Nitrogen-Metabolizing Bacteria and Alleviates the Decomposition of Amino Acids and Urea In Vitro

Abstract: Biochanin A is a naturally occurring flavonoid compound that is found in plant species such as red clover (Trifolium pretense) and alfalfa (Medicago sativa). Flavonoids have been reported to regulate ruminal fermentation, and the objective of this study was to evaluate the effects of biochanin A on ruminal microbial composition and nitrogen metabolism. The experiment was performed by in vitro batch culturing of a control (without biochanin A) and a biochanin A treatment. Following a 24-h incubation, gas produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Natural products (mostly secondary metabolites from plants such as tannins, saponins and essential oils) are sources of potential compounds for urease inhibition ( Modolo et al., 2015 ). Most recently, Liu et al. (2020) reported that Biochanin A (a natural compound) effectively inhibited rumen urease and subsequent urea degradation, thereby reducing rumen NH 3 production.…”
Section: Factors Affecting Urea Hydrolysis and Transportation In The Rumenmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products (mostly secondary metabolites from plants such as tannins, saponins and essential oils) are sources of potential compounds for urease inhibition ( Modolo et al., 2015 ). Most recently, Liu et al. (2020) reported that Biochanin A (a natural compound) effectively inhibited rumen urease and subsequent urea degradation, thereby reducing rumen NH 3 production.…”
Section: Factors Affecting Urea Hydrolysis and Transportation In The Rumenmentioning
confidence: 99%
“…In our previous research, we investigated efficient urea utilization mechanisms; and factors affecting urease activity such as dairy cow immunization against ureases in the rumen ( Zhao et al., 2015 ), and urease inhibitory compounds ( Liu et al., 2020 ). We have also published a review about ruminal microbial urease activation, ureolytic bacteria diversity and urea recycling, but no integrated review about urea transport and hydrolysis ( Jin et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the concentration of NH 3 -N in the rumen could be associated to the degradation of dietary protein and NH 3 -N absorption by ruminal microbes (Belanche et al, 2012;Ushida et al, 1986). In the present study, higher proportions of proteolytic bacteria Selenomonas spp., which significantly increased NH 3 -N production (Liu et al, 2020), was found in sheep rumen. In addition, fibrolytic bacteria are highly dependent on NH 3 -N availability as a source of N (Russel et al, 1992).…”
Section: Discussionmentioning
confidence: 84%
“…A similar result was found by Jelali and Ben Salem (2014) in a study with buffalo calves offered Moringa oleifera leaf that is rich in flavonoids. Liu et al (2020) also reported that flavonoids decrease ruminal NH 3 -N concentrations in in vitro experiments. This would indicate that the AME may reduce ruminal ammonia concentrations by increasing the utilization of amino acids or promoting the synthesis of microbial proteins.…”
Section: Discussionmentioning
confidence: 89%